Analisis Pengaruh Return On Asset (ROA) Dan Return On Equity (ROE) Terhadap Harga Saham PT. Indosat Tbk - Roslina,; Alwi, (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2021)
Before investing, investors must know and choose stocks that can provide benefits by assessing the ratio of return on assets (ROA) and return on equity (ROE). This study aims to observe and analyze the effect of return on assets (ROA) and return on equity (ROE) on the stock price of Pt. Indosat Tbk. This research is an associative type, using quantitative data from secondary data sources. The population in this study is the Financial Statements of Pt. Indosat, Tbk. Which is calculated from the beginning of going public for the period 1994-2020, which is for 25 years. The sample used is the period 2006-2019, which is 14 years at Pt.IndosatTbk which is listed on the Indonesian stock exchange. The sampling technique used in this study is purposive sampling with the sampling criteria in this study are updated financial statement data for 14 years from 2006-2019. 2019. The research instrument used is in the form of financial statement data consisting of a statement of net income, total assets, total equity and profit and loss of the company to get the share price value for the period 2006-2019. Data collection techniques used are documentation and literature study. The data analysis technique used is the classical assumption test, multiple linear regression analysis, multiple correlation coefficients, determination test, t test and f test. The results showed that return on assets (ROA) and return on equity (ROE) had a significant effect on the stock price of PT. Indosat Tbk.